2000
DOI: 10.1017/s0376892900000266
|View full text |Cite
|
Sign up to set email alerts
|

First-year impacts of shelterwood logging on understory vegetation in an old-growth pine stand in central Ontario, Canada

Abstract: There is evidence in the literature that a variety of logging practices may result in significant short and long-term changes to vegetation in the forest understory, however, these changes are still largely unknown for many forest types. The objective of this study was to determine the short-term effects of shelterwood logging on tree and non-arboreal plant species composition and diversity in both the understory and sapling strata within the Owain Lake Stand of old-growth red and eastern white pine located in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…On the other hand, shelterwood cuts of N. pumilio forests produce local extinctions (e.g., L. alopecurus) of extremely sensitive understory species. This is also observed in boreal forests (Quinby, 2000). The absence of a particular species in post-harvesting years may be attributed to harvesting impacts on microclimatic and site conditions, but also to natural variations in plant life history characteristics, or a combination of these factors (Smith et al, 2008).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…On the other hand, shelterwood cuts of N. pumilio forests produce local extinctions (e.g., L. alopecurus) of extremely sensitive understory species. This is also observed in boreal forests (Quinby, 2000). The absence of a particular species in post-harvesting years may be attributed to harvesting impacts on microclimatic and site conditions, but also to natural variations in plant life history characteristics, or a combination of these factors (Smith et al, 2008).…”
Section: Discussionmentioning
confidence: 85%
“…Species introduction after shelterwood application is also observed in other temperate forests of the world (e.g., Quinby, 2000;Poorbabaei and Poor-Rostam, 2009), and could be a consequence of other human activities too, like livestock (e.g., Ewald, 2000). In South Patagonia, plant dispersion is facilitated mainly by wind (anemochore species) or animals (zoochore species).…”
Section: Discussionmentioning
confidence: 96%
“…These losses could be due to changes in the forest structure, microclimatic conditions or nutrient cycles (Reader and Bricker 1992;Lewis and WhitWeld 1999;Caldentey et al 2001). However, most studies only analyze biodiversity loss in timber-quality forests (Thomas et al 1999;Quinby 2000;Deferrari et al 2001;Spagarino et al 2001;Jalonen and Vanha-Majamaa 2001;Martínez Pastur et al 2002a), without to consider the interaction with remainder site types enclosed in the landscape (Hutchinson et al 1999;Rosso et al 2000;Peh et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Previous work on the effects of forest harvest on understory communities has shown that shrubs tend to become as abundant or more abundant shortly after harvest than they were prior to harvest [5,70,71]. While we don't know whether shrubs differed in abundance between our treatments before fire, our work suggests that the combination of harvesting plus fire in quick succession has a compounding negative effect on shrub recovery.…”
Section: Discussionmentioning
confidence: 54%